Government Support for Innovative Entrepreneurship: Advancing Sustainable and Resilient Business Growth - Pavlovskyi, Serhii; Abuselidze, George; Nurgaliyeva, Ainash; Hryvkivska, Oksana; Kobyelyev, Volodymyr; Lysyi, Vadym (European Journal of Sustainable Development, 2025)
The materials presented by the authors are aimed at studying peculiarities of the current state of public support for business entities, including micro-firms and representatives of medium and small businesses, which are more vulnerable elements of the market economy of the country, especially under conditions of various crises (financial, social and economic, political, cultural, aggravated by pandemic coronavirus infection). The article shows the features and directions of influence of state policy and various programs and planned measures, tools, and means of support (material, informational, legal, etc.) on the development of large, small, and medium businesses in Kazakhstan, considering the experience of foreign developed and developing countries, including in the regional context. The topic chosen by the authors is certainly promising for further scientific and theoretical study, including the study of modern specifics of state support for private enterprise with a comparative analysis of the experience of other countries in this aspect. Keywords: entrepreneurship entities, innovative entrepreneurship, financial support, state programme, innovative development